Maternal undernutrition induces neuroendocrine immune dysfunction in male pups at weaning - Chisari, Andrea Nancy (2001)
The present study was designed to assess the effect of maternal undernutrition, during gestation and lactation, on the neuroendocrine [hypothalamo-pituitary-adrenal (HPA)]-immune axis response to endotoxin (LPS) administration. For this purpose, 21-day-old male rats from both well-nourished (WN) and undernourished (UN) mothers were examined 2 h after injection (i.p.) of vehicle alone (VEH) or containing LPS (130 µg/kg BW). Circulating levels of glucose (GLU), ACTH, corticosterone (B), tumor necrosis factor-alpha (TNFα) and leptin were explored. The results indicate that: (a) mother body weight was significantly (p < 0.05) reduced, as a consequence of UN, at the second and third weeks of pregnancy; (b) no differences in basal glycemia were found in the two groups of pups, and LPS treatment did not induce hypoglycemia, in either group; (c) basal plasma ACTH, B and TNFα levels were similar in the two groups, and LPS-induced ACTH, B and TNFα secretions, although severalfold higher than respective VEH values (p < 0.05) in pups from WN mothers, were fully (ACTH and B) and partially (TNFα) abolished in products from UN mothers; (d) both mean body weights and basal plasma leptin levels were significantly (p < 0.05) lower in pups from UN than from WN mothers, and LPS administration did not modify plasma leptin values in products from both groups. In addition, results of dispersed total adrenal cells incubated in vitro indicate that: (a) both basal and ACTH (22 pM)-induced B secretion were significantly (p < 0.05) lower in cells from UN than WN pups, and (b) leptin (100 nM) was able to inhibit partially ACTH-stimulated B output by adrenal gland (AG) cells from WN pups; however, it failed to inhibit ACTH-stimulated glucocorticoid release by AG cells from UN pups. The present results indicate that undernutrition in mothers, during the very critical periods of gestation and lactation, induces in their male pups at weaning: (a) reduced circulating leptin levels and body weight values; (b) metabolic adaptation to normal carbohydrate metabolism; (c) hyporesponsiveness of the HPA and immune (TNFα) axes during endotoxemia, and (d) leptin resistance at the adrenocortical level. This study strongly supports that undernutrition of mothers results in neuroendocrine immune dysfunction of their pups; however, adrenal resistance to the inhibitory effect of leptin on glucocorticoid output is developed, probably as an adaptive mechanism to counteract unfavorable metabolic conditions.